"Contaminación acústica por fuentes móviles: caso mini terminales vía a El Empalme y vía a Buena Fe del cantón Quevedo". - Zambrano Palma, Marian Joyce (2022)
The purpose of the research was to identify the noise pollution levels of the Mini terminal of the Vía a El Empalme and the Mini terminal of the Vía a Buena Fe. For this purpose, a methodological design with a quantitative approach was applied, the methods correspond to inductive deductive , the primary sources correspond to the data taken in situ during a different month in each evaluated area, a preliminary baseline and a small survey were carried out to know the citizen perception of the Miniterminals, the sample